2020
DOI: 10.1007/s43440-020-00125-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of nicotinamide and l-arginine against monocrotaline-induced pulmonary hypertension in rats: gender dependence

Abstract: Background The purpose of this paper was to examine the effects of nicotinamide (ND) and l-arginine (l-ARG) on pulmonary vascular and heart changes induced by pulmonary hypertension in rats in a gender-dependent way. Methods Experiments were performed on male (M) and female (F) rats. PAH was induced via monocrotaline injection (sc, 60/kg B.W.) on day one of the 23-day observational period. After that, the animals were sacrificed, hearts removed and weighed and the papillary muscles isolated to measure force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The observed decrease in nicotinamide may be related to its higher use in the nicotinamide phosphoribosyltransferase reaction that promotes pulmonary vascular remodeling in the development of pulmonary arterial hypertension ( Chen et al, 2017 ), a common finding in chronic hypoxia ( Ottolenghi et al, 2020 ; Gassmann et al, 2021 ). As a matter of facts, either nicotinamide ( Sztormowska-Achranowicz et al, 2020 ) or niacin (or nicotinic acid; Jia et al, 2020 ) are being investigated as drugs to ameliorate progression of hypoxia-induced pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The observed decrease in nicotinamide may be related to its higher use in the nicotinamide phosphoribosyltransferase reaction that promotes pulmonary vascular remodeling in the development of pulmonary arterial hypertension ( Chen et al, 2017 ), a common finding in chronic hypoxia ( Ottolenghi et al, 2020 ; Gassmann et al, 2021 ). As a matter of facts, either nicotinamide ( Sztormowska-Achranowicz et al, 2020 ) or niacin (or nicotinic acid; Jia et al, 2020 ) are being investigated as drugs to ameliorate progression of hypoxia-induced pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, as nitric oxide precursors, citrulline and arginine present a cardioprotective function . It has been demonstrated that plasma levels of arginine and citrulline dropped precipitously after congenital cardiac surgery, while citrulline and arginine supplementation played a protective role in PAH. , Furthermore, in patients with preserved ejection fraction heart failure, administration of arginine and citrulline contributed to an improvement in pulmonary vascular resistance as well as the right ventricular ejection fraction, thereby improving the right ventricular function . Collectively, the decreased level of these amino acids may be hallmarks of a dysregulated RV function in PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reveal that patients with pulmonary arterial hypertension had lower α-tocopherol nicotinate levels and, similarly, lower antioxidants levels . Nicotinamide played an active role in the process of right ventricular function or pulmonary vascular remodeling, so it can improve the changes of pulmonary vascular and cardiac function in rats with pulmonary hypertension . Alleviation of renal impairment through the pathway linked to nicotinamide N -methyltransferase (NNMT) expression contributed to control of the progression of hypertensive nephropathy .…”
Section: Discussionmentioning
confidence: 99%
“…77 Nicotinamide played an active role in the process of right ventricular function or pulmonary vascular remodeling, so it can improve the changes of pulmonary vascular and cardiac function in rats with pulmonary hypertension. 78 Alleviation of renal impairment through the pathway linked to nicotinamide N-methyltransferase (NNMT) expression contributed to control of the progression of hypertensive nephropathy. 79 Nicotinamide nucleotide transhydrogenase activity affected the redox balance of mitochondria and the development of hypertension in mice.…”
Section: Discussionmentioning
confidence: 99%